Isolated Distal Ulna shaft fracture with Distal Radioulnar Joint dislocation or Reverse Galeazzi Pattern: A Case Report with Literature Review - Ranjeet Choudhary; Ramesh Negi; Devender Kasotya; Harshit Verma; Sukhmin Singh (Journal of Orthopaedic Case Reports)
Introduction: Galeazzi fracture is known as the fracture of the distal end radius with distal radioulnar joint dislocation. Many patterns are described in literature which are equivalent but the distal ulna shaft fracture with distal radioulnar joint dislocation is rarely mentioned. We present a case report of this rare pattern. Case Report: A 20-year-old male presented to our emergency department with complaints of pain and swelling over the left wrist. After initial assessment, radiographs of the wrist with forearm and hand were taken. Radiograph revealed a distant pattern of fracture which was distal 3rd of ulna shaft fracture with distal radioulnar joint dislocation. The patient was planned for operative intervention and open reduction internal fixation was done using a standard low contact dynamic compression plate and k-wire fixation for DRUJ. Postoperative DASH score after 18 months is 19.2. After 2-year follow-up, the patient has full range of motion at wrist without any pain and no arthritic changes. Conclusion: With the ulna shaft fracture, DRUJ is usually not involved. Ulna shaft fracture with DRUJ dislocation is a rare injury which if promptly managed early with surgical intervention yields satisfactory results.